On What Is Personally Appealing on Conceptual Relativism - Dancák, Daniel (Philosophy and Canon Law, 2023)
Conceptual relativism is not an attractive position. Surely, it has its ups and downs, but the ups are rarely mentioned. This article has no ambition to provide a resolute groundbreaking argument in favour of the conceptual realism. It only aims to reconstruct the very basis of the given position from the defendant’s point of view, while giving a bit of a personal (or existential if you will) touch to the whole topic.The personal element in question resides in the fact that there are incommensurable percepts, experiences, even worlds which all “feel” equally real to the subjects. This is something to what realism does not seem to be able to do justice without diminishing the ontological status of the “wrong” opinions, beliefs, etc., but this does not seem to go well with how we experience our “imperfect” realities. Conceptual relativists, however, are free from strictly distinguishing between correct and incorrect views on reality and, thus, they are able, if nothing else, to retain and appreciate the reality of our subjective worlds.